Problems associated with evaluation of Extension of Time (EOT) claim in government projects [electronic resource] - Siti Aisah Mat Isa, 1987- author; Maizon Hashim; Fakulti Alam Bina (2014)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2014